The selection of water property formulae for volume and flow calibration and measurement*This updates the paper first published in [001]. (14th September 2018) - Batista, Elsa; Paton, Richard
Abstract: When employing gravimetric or volumetric methods for calibrating volumetric measures, proving tanks, pipe provers and flowmeters, water is often used as the calibration medium. Knowledge of the density of water is required along with other properties such as compressibility, viscosity and speed of sound. In the scientific literature, different formulae are proposed to express these properties of water. This is particularly noticeable for formulae for the density of water where different formulae have been taken into International Standards from ISO, OIML, API and the EI. The difference in formulae does not generally give rise to significant differences in density however even small inconsistencies may cause problems for trade when differences in the value of a product occur. It has also been evident that some formulae are being specified and used outside their range of applicability. In this paper, some of the most commonly referenced expressions have been summarised and compared. As initially the referenced formulae are all for pure water, the paper recognises that impure water, from potable drinking water through to brine may be used. Formulae to express the properties of saline water have therefore also been identified. The aim of the paper is to provide a set of practical formulae which can be used to reduce differences in measurement, ensure low uncertainties for measurement, and provide a reference source to identify un-attributed formulae where they occur. Practical formulae have been proposed and will apply equally to measurement at the highest levels of volume determinations through to industrial and scientific volume and flow measurement applications using water across a temperature range 0 °C–90 °C and salinity 0 to 120 g kg −1 .